Retinal hamartomas at different stages in a patient with tuberous sclerosis: A OCT‐SS description - Paula Basso Dias; Anna Carolina Badotti Linhares; Kenzo Hokazono (Clinical Case Reports, 2023)
Key Clinical Message Retinal astrocytic hamartoma (RAH) is a benign glial tumor that may be present in patients with tuberous sclerosis (TS), contributing to the diagnosis of this syndrome. While hamartomas identified through indirect ophthalmoscopy are often large enough to affect vessels and optic disc anatomy, RAH not detected in previous fundoscopies may become apparent in optical coherence tomography (OCT). The purpose of this report was to describe and characterize RAH with OCT with swept‐source technology (OCT‐SS), aiming to establish a more comprehensive classification for these hamartomas due to their diverse presentations. Fundus examination of a 11‐year‐old girl revealed retinal tumors in both eyes. OCT‐SS confirmed the diagnosis of TS, revealing dome‐shaped hyperreflective masses at different stages of evolution. Lesion 1: maximum thickness (MT) of 336 μm and ganglion cell layer disorganization. Lesion 2: MT of 438 μm and preserved outer plexiform layer. Lesion 3: posterior shadow, MT of 1478 μm and complete rupture of retinal anatomy. Lesion 4: MT of 342 μm and preserved retinal anatomy. OCT is a noninvasive method which assists the diagnosis of subclinical lesions and clinical characterization of TS patients.